2018
DOI: 10.1038/s41598-018-28777-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein (LDL)-dependent uptake of Gram-positive lipoteichoic acid and Gram-negative lipopolysaccharide occurs through LDL receptor

Abstract: Lipoteichoic acid (LTA) and lipopolysaccharide (LPS) are bacterial lipids that stimulate pro-inflammatory cytokine production, thereby exacerbating sepsis pathophysiology. Proprotein convertase subtilisin/kexin type 9 (PCSK9) negatively regulates uptake of cholesterol by downregulating hepatic lipoprotein receptors, including low-density lipoprotein (LDL) receptor (LDLR) and possibly LDLR-related protein-1 (LRP1). PCSK9 also negatively regulates Gram-negative LPS uptake by hepatocytes, however this mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 59 publications
3
48
0
Order By: Relevance
“…We could not detect any differences in the levels of plasma PCSK9 between patients with Gram‐negative or Gram‐positive infections. This is in accordance with findings that the major lipoproteins of both Gram‐negative (LPS) and Gram‐positive (LTA) bacteria are removed from the circulation in an LDLR/PCSK9‐dependent manner .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We could not detect any differences in the levels of plasma PCSK9 between patients with Gram‐negative or Gram‐positive infections. This is in accordance with findings that the major lipoproteins of both Gram‐negative (LPS) and Gram‐positive (LTA) bacteria are removed from the circulation in an LDLR/PCSK9‐dependent manner .…”
Section: Discussionsupporting
confidence: 92%
“…Proprotein convertase subtilisin/kexin enzyme 9 levels are elevated by an inflammatory response and in critically ill ICU patients , but how PCSK9 levels vary in different types of bacterial infections has not previously been explored. Our bacteraemia cases had a median day 0 PCSK9 level of 376 ng mL −1 , which is approximately double the value reported in a meta‐analysis of 15 cholesterol studies (final pooled 95% confidence interval 170–220 ng mL −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro study, the concentration of LPS is varied. Some studies used 2.5 or 1 µg/mL LPS to stimulate HepG2 cells to produce proinflammatory factors . Another study found that when the LPS concentration was 40 µg/mL, LO2 cell expression of proinflammatory factors peaked .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic factors of P. aeruginosa mainly based on lipopolysaccharide (LPS), flagella endotoxin and extracellular toxin [16]. Most of the Gram-positive pathogens depends on, lipoteichoic acid, which induce pro-inflammatory cytokines mediates by Toll-like receptor 4 is a protein (TLR-2) [17,18]. But Non-pathogenic Gram-positive bacteria, such Pediococcus, Enterococcus, Lactobacilli , persuade a dissimilar pattern of cytokines in peripheral blood cells[1921].…”
Section: Introductionmentioning
confidence: 99%